PERUNDUNGAN PADA REMAJA DI MASA PANDEMI COVID-19 - Fitriyani, Lia; Nugraha, Dadi Mulyadi; ., Supriyono (Universitas Negeri Semarang, 2021)
During the pandemic, activities are carried out from home, as well as school activities that require students to study at home. Even so, it doesnâ€™t rule out bullying in adolescents during a pandemic. This study aims to determine the effect of Pancasila values in preventing bullying in adolescents during the covid-19 pandemic. This research uses quantitative methods and descriptive analysis. To obtain data, this was done by distributing questionnaires filled out by 42 respondents. The findings obtained, 83,3% of respondents stated that the values of pancasila affect the development of adolescents and the rest stated â€œmaybeâ€. Other findings, 95,2% respondents stated that bullying during the pandemic was due to a lack of understanding of the values of Pancasila and 4,8% stated â€œnoâ€. Then as many as 73,8% of respondents stated that the exixtence of a pandemic which resulted in schools being conducted remotely was a factor in the occurence of bullying during the pandemic period and 26,2% said â€œnoâ€. Then, 95,2% of respondents stated that the role of parents and teachers is very important during the pandemic. Therefore, the influence of Pancasila values to prevent bullying this pandemic is very important and must be used as a basis for adolescents in their behavior so that deviant and detrimental behavior doesnâ€™t occur, especially during the pandemic, which is a new situation. Masa pandemi membuat kegiatan dilakukan dari rumah, begitupun dengan kegiatan sekolah yang mengharuskan para siswa belajar di rumah. Walaupun begitu tidak menutup kemungkinan terjadinya perundungan pada remaja di masa pandemi. Penelitian ini bertujuan untuk mengetahui pengaruh nilai-nilai Pancasila dalam mencegah terjadinya perundungan pada remaja di masa pandemi covid-19. Penelitian ini menggunakan metode kuantitatif dan analisis deskriptif. Untuk memperoleh data, dilakukan dengan menyebarkan kuesioner yang diisi oleh 42 orang. Hasil temuan yang diperoleh, 83,3% responden menyatakan bahwa nilai-nilai Pancasila berpengaruh terhadap perkembangan remaja dan sisanya menyatakan â€œmungkinâ€. Temuan lainnya, 95,2% responden menyatakan perundungan di masa pandemi akibat kurangnya pemahaman nilai-nilai Pancasila dan 4,8% menyatakan â€œtidakâ€. Lalu, sebanyak 73,8% responden menyatakan adanya pandemi yang berakibat sekolaah dilakukan jarak jauh menjadi salah satu faktor terjadinya perundungan di masa pandemi dan 26,2% menyatakan â€œtidakâ€. Kemudian, 95,2% responden menyatakan peran orang tua dan guru sangat penting di masa pandemi. Maka dari itu, pengaruh nilai-nilai Pancasila untuk mencegah terjadinya perundungan di masa pandemi ini sangatlah penting serta harus dijadikan landasan remaja dalam bertingkah laku agar tidak terjadi perilaku menyimpang dan merugikan, terlebih di masa pandemi yang merupakan situasi baru.